2007
DOI: 10.1051/ebr:2007029
|View full text |Cite
|
Sign up to set email alerts
|

Lack of detectable DNA uptake by bacterial gut isolates grownin vitroand byAcinetobacter baylyicolonizing rodentsin vivo

Abstract: Biological risk assessment of food containing recombinant DNA has exposed knowledge gaps related to the general fate of DNA in the gastrointestinal tract (GIT). Here, a series of experiments is presented that were designed to determine if genetic transformation of the naturally competent bacterium Acinetobacter baylyi BD413 occurs in the GIT of mice and rats, with feed-introduced bacterial DNA containing a kanamycin resistance gene (nptII). Strain BD413 was found in various gut locations in germ-free mice at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 42 publications
0
49
0
Order By: Relevance
“…Several bacterial species with the potential to develop competence belong to the common gut microbial community (EFSA, 2009b;Rizzi et al, 2012). However, actual competence development and transformation of such bacteria by genomic DNA of plants has not yet been observed in the lower gastrointestinal tract even with optimised model systems providing a selective advantage (Nordgård et al, 2007;EFSA, 2009b;Rizzi et al, 2012). In contrast, some studies have shown that introduced bacteria can be naturally transformed in the oral cavity of humans and animals (Mercer et al, 1999a(Mercer et al, , b, 2001Duggan et al, 2000Duggan et al, , 2003.…”
Section: Exposure Characterisationmentioning
confidence: 99%
“…Several bacterial species with the potential to develop competence belong to the common gut microbial community (EFSA, 2009b;Rizzi et al, 2012). However, actual competence development and transformation of such bacteria by genomic DNA of plants has not yet been observed in the lower gastrointestinal tract even with optimised model systems providing a selective advantage (Nordgård et al, 2007;EFSA, 2009b;Rizzi et al, 2012). In contrast, some studies have shown that introduced bacteria can be naturally transformed in the oral cavity of humans and animals (Mercer et al, 1999a(Mercer et al, , b, 2001Duggan et al, 2000Duggan et al, , 2003.…”
Section: Exposure Characterisationmentioning
confidence: 99%
“…However, competence development and transformation of such bacteria with genomic DNA of plants has not been observed in the lower gastrointestinal tract, even with optimised model systems providing a selective advantage (Nordgård et al, 2007;EFSA, 2009c;Rizzi et al, 2012). In contrast, some studies have shown that introduced bacteria can be naturally transformed in the oral cavity of humans and animals (Duggan et al, 2000(Duggan et al, , 2003Mercer et al, 1999aMercer et al, ,b, 2001Rizzi et al, 2012).…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%
“…The spread of transgenic plant DNA has been observed from decaying leaves, by simulated rainwater, in field plots, from roots, and via pollen (21,22). While efforts to detect HGT to A. baylyi in the gastrointestinal tracts of insects and animals were unsuccessful, digested transgenic plant tissue in insect fecal matter remains capable of transforming A. baylyi (23)(24)(25)(26). These studies inform continued assessment of HGT and provide insights into ways to design genetically modified organisms to decrease the risk of transgene dissemination.…”
Section: Monitoring Horizontal Gene Transfermentioning
confidence: 99%